IDE516 : Design methods / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2020)
This course is a semester long course conducted to provide students with analytical and methodological thinking to design. The course is conducted such that students will be able to begin applying the design methods into studio class projects. Assignments are strategically carried out after every major topic in the class to enable students to apply the knowledge that were shared in lectures to identify level of student’s understanding in the subject. Final assignments will be conducted to measure the students understanding of design methods leading to design projects the course will also emphasis on current issues and case studies to which students and the instructor will be able to dialogue upon and enhance the course with new and fresh perspective.